2020
DOI: 10.1038/s41598-020-59248-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of perinatal nicotine exposure on genetic profiles of neurons in the sub-regions of the VTA

Abstract: Chronic nicotine exposure during pregnancy has been shown to induce physiological and anatomical alterations in offspring. Previously, we investigated the complexity of dopamine (DA) neuron firing in the sub-regions of the ventral tegmental area (VTA) following perinatal nicotine exposure. Using approximate entropy, we found that within the middle sub-region, the parainterfascicular nucleus (PIF), there was higher complexity indicating more random neural firing and a less homogeneous neuron population. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The main gene expression change happened in TH, DA neurons, in which we observed a consistently increased significance in PN sub-region compared to PIF and PBP at P7 PN vs PBP (p < 0.01), at P14 PN vs PIF (p < 0.05) and PN vs PBP (p < 0.05) and at P21 PN vs PIF (p < 0.05) and PN vs PBP (p < 0.05). This significance in expression of the DA neurons in the PN sub-region of the VTA in the P14 and P21 groups was consistent with our previous study of 28-day old rat pups, where there was a large increase of relative gene expression in DA neurons in the PN sub-region of the VTA compared to the saline group 12 . We also observed that GABA and glutamate neurons were also developing in the sub-regions of the VTA and dominated different regions of the VTA, acting complementary to the development of the DA neurons.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The main gene expression change happened in TH, DA neurons, in which we observed a consistently increased significance in PN sub-region compared to PIF and PBP at P7 PN vs PBP (p < 0.01), at P14 PN vs PIF (p < 0.05) and PN vs PBP (p < 0.05) and at P21 PN vs PIF (p < 0.05) and PN vs PBP (p < 0.05). This significance in expression of the DA neurons in the PN sub-region of the VTA in the P14 and P21 groups was consistent with our previous study of 28-day old rat pups, where there was a large increase of relative gene expression in DA neurons in the PN sub-region of the VTA compared to the saline group 12 . We also observed that GABA and glutamate neurons were also developing in the sub-regions of the VTA and dominated different regions of the VTA, acting complementary to the development of the DA neurons.…”
Section: Discussionsupporting
confidence: 92%
“…Interactions with addictive drugs have shown behaviors of aggression, compulsion, and lack of social play because of the mesocorticolimbic DA circuitry with the NAc and PFC 11 . Previously, our lab published a study that observed the three sub-regions of the VTA in rats following gestational exposure to nicotine at 28 days after birth 12 . Samples were collected from 28-day old rat pups following exposure to nicotine prenatally as well as through breast milk after birth 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutamate pathways are linked to many other neurotransmitter pathways as glutamate receptors are found throughout the brain and spinal cord in neurons and glia 76 . A subset of DA neurons in the VTA co-release DA and glutamate to the NAc and are believed to play a role in behavioral activation following stimulants, illustrating a role in drug addiction 77 79 . This could partly explain the enriched glutamatergic synapse pathway as alcohol directly activates the DA, playing an essential role in neurodevelopment 80 .…”
Section: Discussionmentioning
confidence: 99%